GONÇALO M. TAVARES E O BAIRRO: DAS HETEROTOPIAS ÀS VICISSITUDES DO ABSURDO - Custódio, Robson José (2017)
This dissertation aims to analyze the paths that refers to space and singular language absorbed in the writing of the contemporary Portuguese author Gonçalo M. Tavares within the series The neighbourhood, that currently contains 10 books, and interstice for 29 more, where the author pictures the everyday and together life of different senhores, in a space created by Tavares himself in order to inhabit some intellectuals, as a way of refuge from a world they do not belong to. Therefore, I go through the ideas presented by Foucault, mainly, about heterotopia, the places without place that recover that rebuilding of reality. The neighborhood is a place, so to speak, typically urban, that can put us before relations between the neighbors and make us rediscover our own conceptions about the everyday life, based on a map that projects all the residents and their houses, even those we did not effectively met yet in one of the books. Besides, it is important to emphasize that that space will be set as interminable, also in the presence of and in relation to an “other”, especially from the theoretical discussions by Maurice Blanchot, that enable us to put in an open position each narrative that intertwines gentlemen to gentlemen; looking, still, to the empty houses that are waiting for someone to move in. We start, in the first sections of this discussion, from another Tavares work, Biblioteca, to perceive the notion of infinite, consequential in so many other works of him, where we travel and create possibilities of going beyond and short. Gonçalo, lastly, creates a very close relation in the proposition of rescuing the past before the present, and so walk towards the future of the stories, many times with the resource of intertextuality.